Blended learning reform in English viewing, listening and speaking course based on the POA in the post-pandemic era - Cheng, Jiaxue (Frontiers in Education, 2025)
Previous studies on blended learning in Chinese universities focused on improving language training. However, higher education should also address key competencies and moral education. Therefore, this study constructed a blended learning mode in English Viewing, Listening and Speaking Course based on the Production-Oriented Approach, aiming at solving the traditional drawbacks of language training in this course and implementing cultivation of key competencies, values, and attitudes at the same time. 40 students were invited to participate in the practice of this mode. A pre-test and a post test, students’ productive performance, questionnaires, and teacher’s observation were used to evaluate the effectiveness of this mode. The results showed that this mode could effectively implement both language education and the cultivation of virtues and other key competencies.